2015
DOI: 10.1021/acsami.5b03862
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Aligned Iron Oxide/Gold Nanoparticle-Decorated Carbon Nanotube Hybrid Structure as a Humidity Sensor

Abstract: Functionalized carbon nanotubes (f-CNTs), particularly CNTs decorated with nanoparticles (NPs), are of great interest because of their synergic effects, such as surface-enhanced Raman scattering, plasmonic resonance energy transfer, magnetoplasmonic, magnetoelectric, and magnetooptical effects. In general, research has focused on a single type of NP, such as a metal or metal oxide, that has been modified on a CNT surface. In this study, however, a new strategy is introduced for the decoration of two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…[83][84][85] As a result, their conduc tivity and sensitivity would be orders of magnitude higher than even the best randomly dispersed states of nanoparticles, significantly improving performances of electrodes, superca pacitors, transistors, sensors, actuators, heat exchangers, ther moelectrical converters, optics, and biomedical devices. [86][87][88] The assembly of nanoscale particles can learn from macro scale manufacturing. Traditionally, continuous carbon fibers (CFs) or GF reinforced polymer matrix depends on fiber ori entations for tailored composite mechanics.…”
Section: Motivations For Nanoparticle Alignmentmentioning
confidence: 99%
“…[83][84][85] As a result, their conduc tivity and sensitivity would be orders of magnitude higher than even the best randomly dispersed states of nanoparticles, significantly improving performances of electrodes, superca pacitors, transistors, sensors, actuators, heat exchangers, ther moelectrical converters, optics, and biomedical devices. [86][87][88] The assembly of nanoscale particles can learn from macro scale manufacturing. Traditionally, continuous carbon fibers (CFs) or GF reinforced polymer matrix depends on fiber ori entations for tailored composite mechanics.…”
Section: Motivations For Nanoparticle Alignmentmentioning
confidence: 99%
“…Jaewook et al 160 demonstrated the binary type of NP-CNT composite for humidity sensors using a simple physiochemical method. In a two-step process, rstly positive charge bearing Au particles stacked on the surface of CNT and then gallic acid-modied iron oxide NPs (GA-IONPs) which act as reducing agent to synthesize Au NPs and while mixing with CNT-Au 3+ solution both metal nanoparticles attach on CNT surface through pi-pi interactions (IA-CNT).…”
Section: Gold-cnts Nanostructuresmentioning
confidence: 99%
“…They are used as electrochemiluminescence sensors for the detection of diphenhydramine hydrochloride, humidity sensors, impedimetric immunosensors, electrocatalytic detectors, etc. They are also used in various chemical transformations, some of which are listed in Table .…”
Section: Applications Of Mwcnts and Mwcnt Nanocompositesmentioning
confidence: 99%